2021
DOI: 10.1186/s12935-021-01953-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of RAD51 on the survival and drug responsiveness of ovarian cancer

Abstract: Background Ovarian cancer has greatly endangered and deteriorated female health conditions worldwide. Refinement of predictive biomarkers could enable patient stratification and help optimize disease management. Methods RAD51 expression profile, target-disease associations, and fitness scores of RAD51 were analyzed in ovarian cancer using bioinformatic analysis. To further identify its role, gene enrichment analysis was performed, and a regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…A previous study reported that CTBP1 expression influences DDP resistance of breast cancer cells by activating RAD51 expression ( 19 ). In the present study, RT-qPCR and western blot analysis were used to evaluate the expression of RAD51 in the aforementioned five cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that CTBP1 expression influences DDP resistance of breast cancer cells by activating RAD51 expression ( 19 ). In the present study, RT-qPCR and western blot analysis were used to evaluate the expression of RAD51 in the aforementioned five cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been suggested that inhibition of RAD51 enhances the therapeutic effect of DDP on gastric cancer ( 34 ). Furthermore, CTBP1 influences the DDP resistance of breast cancer cells by activating RAD51 expression ( 19 ). The results of the present study demonstrated that CTBP1 expression was upregulated in DDP-resistant AGS/DDP and HGC-27/DDP gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng Y et al. reported that high RAD51 expression indicated unfavourable survival outcomes and resistance to platinum, taxane, and PARP inhibitors in patients with ovarian cancer [38] . These results are consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, they cannot fully reflect tumor biological characteristics, and individual differences lead to inadequate specificity and incompetence [4,5]. In the past few decades, the rapid and prosperous development of sequencing technology has provided opportunities to systematically explore tumors, and a myriad of genes including RAD51 and PAWR were explored as predictive biomarkers in ovarian cancer [5,7,8]. Due to the intratumor heterogeneity of this deadly disease and the complex molecular mechanisms affecting its prognosis, single factor prediction models usually have low accuracy and efficacy [4,5].…”
Section: Introductionmentioning
confidence: 99%